Evaluating temporal stability of the New Zealand quasigeoid following the 2016 Kaikōura earthquake using satellite radar remote sensing - McCubbine, J.C.; Stagpoole, V.; Caratori Tontini, F.; Featherstone, Will; Garthwaite, M.C.; Brown, N.J.; Amos, M.J.; Fukuda, Y.; Kazama, T.; Takiguchi, H.; Nishijima, J. (OXFORD UNIV PRESS, 2020)
Quasigeoid models can be determined from surface gravity anomalies, so are sensitive to changes in the shape of the topography as well as changes in gravity. Here we present results of forward modelling gravity/quasigeoid changes from synthetic aperture radar data following the 2016 Mw 7.8 Kaikōura earthquake with land uplift of up to 10 m. We assess the impact of the topographic deformation on the reference surface of the New Zealand vertical datum in lieu of costly field gravity field measurements. The most significant modelled gravity and quasigeoid changes are-2.9 mGal and 5-7 mm, respectively. We compare our forward modelled gravity signal to terrestrial gravity observation data and show that differences between the data sets have a standard deviation of ±0.1 mGal. The largest modelled change in the quasigeoid is an order of magnitude smaller than the 57.7 mm estimated precision of the most recently computed NZGeoid model over the Kaikōura region. Modelled quasigeoid changes implied by this particular deformation event are not statistically significant with respect to estimated precision of the New Zealand quasigeoid model.